Research of perfect punctured binary sequence pair in LCZ/ZCZ - XU Lei; JIANG Ting; ZHOU Zheng (Tongxin xuebao)
Perfect punctured binary sequence pair was used in LCZ/ZCZ.The theory of LCZ/ZCZ sequence pair sets was defined,and three new methods for constructing LCZ/ZCZ sequence pair sets were presented: ZCZ sequence pair sets based on odd length perfect punctured binary sequence pairs and Hadamard matrices;LCZ sequence pair sets based on even length perfect punctured binary sequence pairs and modified Hadamard matrices;and ZCZ sequence pair sets based on perfect punctured binary sequence pairs and orthogonal matrices.With the proposed methods,LCZ/ZCZ sequence pair sets have wider range of low/zero correlation zone and larger capacity of LCZ/ZCZ sequence sets,which can satisfy re-quirements of projects application better.